PENGEMBANGAN SISTEM EKONOMI KERAKYATAN DALAM PERSPEKTIF NEGARA HUKUM KESEJAHTERAAN BERDASARKAN UUD 1945 - JS Panjaitan, Marojahan (Sekolah Tinggi Hukum Bandung, 2012)
In the prosperity law state, the most priority is a guarantee for human rights of peoples social economy. In creating human rights of peoples social economy, the state or government is given authority, task or responsibility to get involved and participate in individual or social lives. Then, it produces economy democracy ideology in the field of economy.Keywords: law state, democracy, economy